Incidencia de los precios del petróleo en el crecimiento económico: Reforma a la Ley de Hidrocarburos en Ecuador, en el periodo 1970-2019 - Bolaños Calispa, Islena Dayana (2023)
Economic growth in Ecuador has increased reaching 4.2% in the year 2021, however, its high dependence on oil exports means that the country continues to lag behind in terms of vulnerable employment, corruption and environmental issues, etc. That is why the present investigation aims to determine the effect of oil prices on economic growth: Reform to the Hydrocarbons Law in Ecuador, through an econometric approach, period 1970-2019. For this, data obtained from theAssociation of the Hydrocarbon Industry of Ecuador [AIHE] (2012), the World Development Indicators of the World Bank [WDI] (2021) and the Statistical Review of World Energy [BP] (2021). An Ordinary Least Squares (OLS) model was applied to evaluate the effect between oil prices and economic growth, likewise, aVector Autoregressive (VAR) and Error Correction (VEC) modelto determine the long-term and short-term dynamics, respectively. With this, it was found that Ecuador falls into the so-called <<curse of natural resources>> given the number of oil wells and its low economic growth, in addition, it was determined that there is a short-term relationship, however, in the long term This dynamic is not evident. Finally, it is recommended that the government create a countercyclical oil reserve fund to help mitigate the problems that are generated when there are drops in oil prices and thus counteract the problems that this fact causes in economic growth.